Education and the social construction of 'race' - Figueroa, Peter M. E. (Routledge library editions. Education ;, 2012)
Does the education system help or hinder the fight against racism? This volume provides a constructive critique of the Swan Report of 1985 and of sociological research into racial and ethnic relations. The author undertakes a searching philosophical and sociological analysis of multicultural and antiracist education. He shows how the education system itself can reinforce racist assumptions and behaviour in society, but also argues that through educational and social reconstructing it can promote constructive cross-cultural relations.